Intervention strategies used by teachers to accommodate learners who exhibit emotional and behavioural challenges in Bat cluster in Reigate district, Bulawayo Zimbabwe. - Dima, Lubelihle (Midlands State University, 2018)
Childhood Education (ECE) learners who exhibit behavioural and emotional challenges in Bulawayo African Townships, Reigate District. The objectives were to establish effectiveness of intervention strategies teachers used in identifying Early Childhood Education learners who exhibit emotional and behavioural challenges and to explore intervention strategies teachers‟ use in accommodating learners with selected emotional and behavioural challenges. The study used descriptive research design which was appropriate since it enabled the researchers to describe the situation as it existed. Data from the research instruments was analyzed and presented descriptively. Data was collected through the use of questionnaires for teachers, an interview schedule for School Heads, teachers in charge and senior teachers and observation schedule for learners. The population comprised of ECE teachers, school Heads and TICs. The purposive sample comprised of twenty five teachers, (five teachers from each school) as well as the school heads and ten senior teachers (two teachers from each school one class per school was observed. The study found that the assessment methods teachers used to identify learners with emotional and behavioural challenges were not effective and that teachers in selected schools did not use effective intervention strategies to accommodate ECE learners who exhibit emotional and behavioural challenges. The study recommends that in-service training for teachers be done with a view of equipping them with recent information and that Zimbabwe Institute of Curriculum Development to give guidelines on emotional and behaviour challenges management. The significance of the study findings is that it could help stakeholders to come up with effective intervention strategies in managing learners with emotional and behavioural challenges.